2014
DOI: 10.2337/dc14-0103
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functioning in Children and Adolescents at the Time of Type 1 Diabetes Diagnosis: Associations With Glycemic Control 1 Year After Diagnosis

Abstract: Deficits were evident in neurocognitive functioning within days of diabetes diagnosis that were associated with diabetes outcomes over 1 year postdiagnosis. Impairment was most apparent in psychomotor speed, consistent with research implicating damage to posterior white matter tracts and associated gray matter regions in type 1 diabetes. Psychomotor impairment may be an early marker for a broader neurobehavioral vulnerability that has implications for long-term diabetes management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Another recent DTI study [30••] found a significant association between white-matter structure and A1c at study baseline, but not with a “lifetime” index of A1c, suggesting insult was more likely related to acute (versus chronic) effects of hyperglycemia nearer the time of diagnosis. Our group found a high incidence of impairment in bilateral fine-motor speed, visuomotor integration, and phonemic fluency in children within days of T1D diagnosis [31]. While we do not know whether these acute deficits resolve with a return to euglycemia, impairments in motor speed and working memory were associated with diabetes outcomes over 1 year post-diagnosis, which suggests that acute cognitive dysfunction may be an early marker of neurobehavioral vulnerability.…”
Section: Neurodevelopmental Frameworkmentioning
confidence: 94%
“…Another recent DTI study [30••] found a significant association between white-matter structure and A1c at study baseline, but not with a “lifetime” index of A1c, suggesting insult was more likely related to acute (versus chronic) effects of hyperglycemia nearer the time of diagnosis. Our group found a high incidence of impairment in bilateral fine-motor speed, visuomotor integration, and phonemic fluency in children within days of T1D diagnosis [31]. While we do not know whether these acute deficits resolve with a return to euglycemia, impairments in motor speed and working memory were associated with diabetes outcomes over 1 year post-diagnosis, which suggests that acute cognitive dysfunction may be an early marker of neurobehavioral vulnerability.…”
Section: Neurodevelopmental Frameworkmentioning
confidence: 94%
“…In one study of children newly diagnosed with diabetes (32), deficits were found in psychomotor speed that were associated with metabolic control 1 year later, suggesting that impaired motor speed may be an early marker for cognitive changes that can have a long-term effect on diabetes control.…”
Section: When Should Screening Occur?mentioning
confidence: 99%
“…Nursing staff were taught to administer the measure with a high degree of reliability, and empirically derived cutoffs identified cognitive impairment with good accuracy (49). No comparable tests have been identified as gold-standard instruments for cognitive screening in type 1 diabetes, although there is evidence that the Grooved Pegboard Test (50) may be particularly sen-sitive to diabetes-related cognitive dysfunction (32,5153). …”
Section: How To Screen For Neurocognitive and Executive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) In elderly non-diabetic populations, psychomotor slowing warns of future disability,(9, 10) dementia, (11) and death. (12) Characterizing psychomotor slowing in T1D is likely to become a public health priority in future years, considering the rising incidence of T1D (13) in conjunction with the increased life expectancy of people with T1D.…”
Section: Introductionmentioning
confidence: 99%